ANOD phase 2 improvements on a cost-effective GPS-tracked data logging drifter with GSM and parameter gathering capabilities - Catolico, Clarence Joy V. (2011)
Oceanographic Analysis is a very large area of research and water drifters are tools used in this field to study wave current trajectories. Costs of drifters however are quite high. This motivation has led to the development of ANOD, a cost-effective drifter technology system that can be used by marine scientists in the Philippines. The first phase of ANOD developed a drifter technology that implemented three main functions: sensing, localization, and telemetry. The objective was to come up with a Global Positioning System (GPS) tracked data logging and parameter gathering device with a Global System Mobile (GSM) module which can gather and send data such as wave current direction, salinity and temperature. The second phase of ANOD focuses on the improvement of the first system in terms of deployability, power efficiency and reliability issues, which surfaced as the main predicaments during the deployment of the ANOD Phase 1 drifters. ANOD Phase 2 implemented the drifter system into a new platform which is an ultra-low power microcontroller. The sensing block included sea-surface temperature, salinity and a sea-state sensing capability with gyroscope. Improvements on the accuracy of the sensors were made possible by making the ADC resolution higher and by conducting more test calibrations. The localization was provided by a new GPS module that gathers the longitudinal and latitudinal coordinates and the time. All data gathered are being sent to a base station via GSM and stored to a microSD. The enclosure was also modified to allow the introduction of a solar panel which aims to utilize solar radiation for battery charging. The drifter system was successfully integrated and has been initially deployed and tested in Matnog, Sorsogon. The project ANOD has proven that it is indeed possible to develop low-cost alternatives for drifter systems which can serve the same functions as the expensive and commerically available ones.